2016
DOI: 10.1002/ps.4370
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and insecticidal activity of novel pyrimidine derivatives containing urea pharmacophore against Aedes aegypti

Abstract: A practical synthetic route for pyrimidine derivatives is presented. This study suggests that these pyrimidine derivatives exhibit some activity against the yellow fever mosquito and, with further structure modification, could be novel lead compounds for the development of insecticides against mosquitoes. © 2016 Society of Chemical Industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
44
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 80 publications
(46 citation statements)
references
References 28 publications
1
44
1
Order By: Relevance
“…Previously, our group has synthesised a series of new compounds as pesticides . In this paper the fungicide tebufloquin was selected as a lead compound.…”
Section: Introductionmentioning
confidence: 99%
“…Previously, our group has synthesised a series of new compounds as pesticides . In this paper the fungicide tebufloquin was selected as a lead compound.…”
Section: Introductionmentioning
confidence: 99%
“…In recent reference, her group 17 built a modelling of the P. capsici cellulose synthase 3. In our previous work [18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35] , many bioactive compounds were designed and synthesised. In this paper, based on the structure of seven commercialised CAA fungicides, we found that they have similar structural fragments: amide bond, para-substituted phenyl, 3,4-dialkyloxy substituted phenyl.…”
Section: Introductionmentioning
confidence: 99%
“…Heterocyclic compounds have become the mainstream of new pesticide research due to their wide range of biological activities, low toxicity, high efficiency, environmental friendliness, and structural diversity . Heterocyclic agrochemicals containing nitrogen has better activity, including insecticidal , antimicrobial , antiviral , fungicidal , and herbicidal . Quinolines are one of the most important compounds in nitrogen‐containing heterocycles and exhibited appreciable fungicidal activity .…”
Section: Introductionmentioning
confidence: 99%